Evolution of life history traits in Asian freshwater prawns of the genus Macrobrachium (Crustacea: Decapoda: Palaemonidae) based on multilocus molecular phylogenetic analysis - Wowor, D. (2014)
10.1016/j.ympev.2009.01.002